Intratumoral high endothelial venules in solid tumors: a pooled study - Wang, Bin; Han, Yin; Liu, Jie; Zhang, Xinyao; Deng, Yaotiao; Jiang, Yu (Frontiers in Immunology, 2024)
Objective We performed this pooled analysis for the first time to comprehensively explore the prognostic value of tumor-associated high endothelial venules (TA-HEVs) and determine their relationships with clinicopathological features in solid tumors. Methods Four online databases, including PubMed, Web of Science, Embase, and Cochrane Library, were comprehensively searched to identify studies assessing the effect of TA-HEVs on prognosis or clinicopathological features. Hazard ratios (HRs) with 95% confidence intervals (CIs) were applied to evaluate survival outcomes, including overall survival (OS), disease-free survival (DFS), progression-free survival (PFS), and cancer-specific survival (CSS). The association between TA-HEV status and the clinicopathological characteristics was assessed by odds ratios (ORs) combined with 95% CIs. Subgroup analysis was conducted to explore sources of heterogeneity. The sensitivity analysis was performed to evaluate the stability of our findings. Results A total of 13 retrospective cohort studies, involving 1,933 patients were finally included in this meta-analysis. Effect-size pooling analysis showed that the positivity of TA-HEVs was related to improved OS (pooled HR: 0.75, 95% CI: 0.62-0.93, P<0.01), and DFS (pooled HR = 0.54, 95% CI = 0.41-0.72, P< 0.01). However, TA-HEV positivity in solid tumors was not linked to PFS (pooled HR = 0.75, 95% CI 0.34-1.64, P = 0.47) or CSS (pooled HR: 3.28, 95% CI: 1.03-10.42, P= 0.07). Further subgroup analysis demonstrated that ethnicity and source of HR were the main factors contributing to heterogeneity. Moreover, TA-HEVs were inversely associated with lymph node metastasis and distant metastasis, but were positively related to worse tumor differentiation. However, TA-HEVs were not significantly correlated with sex, LVI, clinical stage, and depth of invasion. Sensitivity analysis suggested that the pooled results were stable and reliable, with no significant publication bias in all included articles. Conclusions This is the first comprehensive analysis of the prognostic value of TA-HEVs in solid tumors using existing literature. Overall, our study demonstrated a significant correlation between TA-HEVs and prognosis as well as clinicopathological features. TA-HEVs may serve as nove immune-related biomarkers for clinical assessments and prognosis prediction in solid tumors. Keywords: solid tumor, high endothelial venules, prognosis, clinicopathological parameters, immunotherapy